Cluster Analysis of Food Consumption Patterns among Women of Reproductive Age in Indonesia - Humayrah, Wardina; Hardinsyah; Tanziha, Ikeu; Fahmida, Umi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
The aim of this study was to cluster the provinces based on the Food Consumption Patterns (FCP) of the Women of Reproductive Age (WRA). This study used secondary data from the 2014 Indonesia Total Diet Study conducted by the Ministry of Health Indonesia. The final subjects included 40.954 healthy WRA aged 15-49 years old. FCP was calculated based on energy adequacy of WRA of nine major food groups for each province. The hierarchical clustering with Ward's method was applied to cluster the FCP of WRA. The results showed that three clusters of FCP were found. The first cluster was characterized by higher intake of cereals and animal foods, but lower intake of tubers, vegetables, and fruits, which implies a high risk of vitamin B6 and C deficiencies. The second cluster was characterized by higher intake of pulses, oil and fat, oily seeds, and sugar, but lower intake of vegetables and fruits as well as animal source foods, which implies high risk in vitamin B1, B3, and B12 deficiencies and overweight. The third cluster was characterized by higher intake of tubers, fruits, and vegetables but lower intake of animal sources foods, pulses, added fat and oily seeds, which implies a high risk in animal protein, fat, calcium, iron, vitamin B2, and folic acid deficiencies.